'I don't feel like I'm in this on my own': Peer support for mothers of children with intellectual disability and challenging behaviour. (September 2019) - Dew, Angela; Collings, Susan; Dowse, Leanne; Meltzer, Ariella; Smith, Louisa
This article reports on the peer support experiences of mothers with a son or daughter with intellectual disability and challenging behaviour. Engagement in parent peer support programs can improve family quality of life and may have multifaceted benefits at the interpersonal, intra-individual self-change and sociopolitical levels. Thirteen mothers were interviewed about their experiences of participating in a parent peer support program. Thematic analysis focused on the process elements of the program that contributed to its effectiveness in providing support to parents. There were three process-related themes: the role of a paid coordinator, diversity of engagement strategies and matching of peer support partners. Mothers appreciated the opportunities provided to engage in a range of strategies tailored to individual preferences, time and capacity constraints, supported by the paid coordinator. One-to-one peer support proved difficult to sustain given the challenges mothers faced in their day-to-day lives.